Computer research on the influence of the peltier effect on the crystallization process of Ві2Те3 based thermoelectric materials - Anatychuk, L.I.; Nitsovich, O.V. (Journal of Thermoelectricity, 2019)
The article presents the results of computer simulation of the process of growing Ві2Те3 based thermoelectric materials by the vertical zone melting method with regard to the Peltier effect occurring at the interface between solid and liquid phases of the grown material when electric current is passed through an ingot. Bibl. 7, Fig. 6, Tabl. 1.